Comparative study of the usability of two software programs for visualization and analysis of digital orthodontic models - Matheus Felter; Milena de Moraes Oliveira Lenza; Maurício Guilherme Lenza; Wendel Minoro Muniz Shibazaki; Rhonan Ferreira Silva (Tabriz University of Medical Sciences, 2018)
Background. Software programs for visualization and analysis of digital orthodontic models, apart from presenting the necessary features for diagnosis and treatment planning, also need to be user-friendly. This characteristic refers to software' usability, a measure that evaluates how easy it is to use it is by a specific group of professionals. The aim of this study was to compare the usability of free available versions of two software programs for visualization and analysis of digital orthodontic models. Methods. Digimodel® and OrthoCAD® usability were evaluated through their interface analysis and executing the following procedures: malocclusion classification and models analysis (arch-length and tooth-size discrepancies). Results. Digimodel® and OrthoCAD® software programs had an installer only for Windows platform, occupied less than 110 megabytes of virtual space and only read files from their respective manufacturers. None possessed Portuguese as a language option. Both allowed visualization of the models in different axes through options present in initial screen, at a click. For model analysis, both software programs required to measure tooth to tooth and performed necessary calculations automatically. However, OrthoCAD® software program was less intuitive because the option for these actions was among several others, within menus, which could cause confusion during navigation. In addition, the marking of points did not always obey the clicked site. Conclusion. The free access version of the evaluated software programs exhibited usability limitations related to language, supported file format and even the model analysis execution for orthodontic diagnosis. Although OrthoCAD® was inferior, both did not meet orthodontists' clinical demand against these factors in the evaluated versions.